Effect on surgical decisions: Ulipristal acetate as key player in Belgian phase IV registration trial. Issue 3 (30th September 2019) - Verguts, Jasper; Godin, Pierre Arnaud; De Vree, Bart; Donnez, Olivier; Cosyns, Stefan; Luyckx, Mathieu; Nisolle, Michelle
Abstract: Objective: To observe alterations in surgical planning that were due to the use of ulipristal acetate (UPA) 5 mg daily for symptomatic uterine fibroids. Methods: A prospective cohort trial involving women with symptomatic fibroids was undertaken in 23 clinical practice sites within Belgium between October 1, 2014, and March 31, 2016, to compare initial surgical planning to performed surgical procedures following the use of UPA 5 mg daily for 3 months. Secondary outcomes were surgical complications, reduction in fibroids, bleeding control, and adverse effects. Results: Two hundred and twenty‐two women were recruited for the trial. The requirement for surgery decreased with the use of UPA, with 54% of women undergoing surgery after treatment. The reduction in surgery performed was lower for women willing to conceive (40%) compared to women who were not (49%). The volume of the fibroids decreased significantly, with the largest measured fibroid decreasing by 50%. Bleeding and pain were significantly decreased with the use of UPA. No major complications were recorded, and no liver function abnormalities were reported during the treatment and in follow‐up. Conclusion: By administering UPA, the required rate of surgery was significantly decreased. Also, the resulting reduction in size of the fibroids could have the potential benefit of reducing surgery‐related complications, and long‐term use may be warranted to avoid surgery completely. Abstract : Administration of ulipristal acetate in women with symptomatic fibroids reduced associated surgery in almost half of patients.